Outcomes of biliary and pancreatic drainage for cases with perforation related to duodenal papillary treatment - Kayashima, Atsuto; Iwasaki, Eisuke; Tamagawa, Hiroki; Machida, Yujiro; Kawasaki, Shintaro; Fukuhara, Seiichiro (Tando, 2021)
A 47-year-old man took ERCP for common bile duct stones. Although the endoscopic sphincterotomy (EST) was performed, it was difficult to grasp and crush the stones. Five hours after the ERCP, his abdominal pain worsened, and then duodenal perforation was recognized by computer tomography. Naso-drainage tubes were inserted into the bile tract and pancreatic duct by urgent ERCP. Since then, the inflammation induced by perforation has gradually improved, and he was discharged 20 days after the procedure. In our hospital, we experienced 2 cases of perforation associated with EST and 2 cases of perforation associated with endoscopic papillectomy. In these cases, biliary and pancreatic drainage was performed for 3 cases, while 1 case who did not undergo drainage finally required surgery. We experienced a case that urgent drainage for biliary and pancreatic duct might be effective for cases with perforation around Vater's papilla.